ANALISIS KARAKTERISTIK FKTP YANG BERMITRA DENGAN BPJS KESEHATAN SEMARANG TERHADAP INDIKATOR KAPITASI BERBASIS KINERJA 2024 - Den, Emilia Van; Maharani, Chatila; Fauzi, Lukman; Indrawati, Fitri (Jurnal Manajemen Kesehatan Indonesia, 2025)
Equal access to health services remains a challenge in achieving Universal Health Coverage (UHC), including in Indonesia. One of the efforts to improve access and the quality of services at Primary Health Care Facilities (PHCFs) is the implementation of the Performance-Based Capitation (PBC) system, which includes indicators such as the Contact Rate, Non-Specialist Referral Ratio, and Controlled Prolanis Participant Ratio. However, the achievement of these indicators has not yet been fully optimized. In 2022, national data showed that the Controlled Prolanis Participant Ratio indicator reached only 3.78% of the ≥5% target. Meanwhile, in the first semester of 2024, the average Contact Rate achievement at BPJS Kesehatan Semarang was only 149.14‰, slightly below the ≥150‰ target. Efforts to optimize PBC performance require in-depth analysis of the factors that influence it, including the characteristics of PHCFs. This study aims to analyze the relationship between the characteristics of PHCFs and PBC indicators. This research is a quantitative analytical observational study with a cross-sectional design, using PBC indicators data from the second semester of 2024 obtained from BPJS Kesehatan Semarang. The sample includes all PHCFs that are contracted partners and receive capitation payments from BPJS Kesehatan Semarang. Data were analyzed using univariate, bivariate, and multivariate analysis with SPSS Statistics. PHCF characteristics that were significantly associated with PBC indicators (p < 0.05) included type of PHCF, ownership status, and number of registered participants